Culture and power : Tuscany and its universities 1537-1609 - Davies, Jonathan, 1966- (Education and society in the Middle Ages and Renaissance, 2009)
Challenging absolutist interpretations, this title presents a study that uses the universities of Pisa and Siena to reveal the contradictions and the tensions as well as the innovations and the traditions which characterised the grand duchy of Tuscany and its cultural politics.